2022
DOI: 10.1590/s1984-29612022016
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c oxidase subunit 1 gene reveals species composition and phylogenetic relationships of Oesophagostomum spp. infecting pigs in northeastern Brazil

Abstract: Helminths of the genus Oesophagostomum cause enteric diseases and affect domestic animals such as pigs. The aim of this study was to explore the species composition and genetic diversity of Oesophagostomum spp. infecting pigs in close contact with humans in the state of Piauí, Brazil. Eighty-seven fecal samples were collected for parasitological tests and molecular analysis. Through microscopy, the overall positivity rate for strongyliform eggs was 81.6% among the pigs studied. Forty-two strongyliform egg samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(24 reference statements)
1
2
0
Order By: Relevance
“…In this research work, 0.7–1 % and 0.4 % variation in sequence identities were observed in ITS 2 sequences among O. columbianum and O. asperum isolates, respectively. The value of disparity exactly coincides with the variation of reference sequences from China and Brazil ( Bacelar et al, 2022 , Li et al, 2016 , Zhao et al, 2014 ). However, divergence (0–1.5 %) was also reported among O. asperum isolates from Shaanxi province and Hunan province, China ( Li et al, 2016 , Yu et al, 2012 ).…”
Section: Discussionsupporting
confidence: 74%
“…In this research work, 0.7–1 % and 0.4 % variation in sequence identities were observed in ITS 2 sequences among O. columbianum and O. asperum isolates, respectively. The value of disparity exactly coincides with the variation of reference sequences from China and Brazil ( Bacelar et al, 2022 , Li et al, 2016 , Zhao et al, 2014 ). However, divergence (0–1.5 %) was also reported among O. asperum isolates from Shaanxi province and Hunan province, China ( Li et al, 2016 , Yu et al, 2012 ).…”
Section: Discussionsupporting
confidence: 74%
“…In the present study, the Strongylida genera infecting pigs were Oesophagostomum , Hyostrongylus , and Trichostrongylus , parasites usually present in swine extensively raised. In a previous work, we demonstrated that the Oesophagostomum species characterized in pigs in the region by cox 1 partial sequencing were O. dentatum , O. quadrispinulatum , and O. columbianum , although the latter is a parasite usually found in goats and sheep [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Necator suillus is a hookworm species described in pigs for almost a century [14], and investigations into its validity, occurrence, epidemiology, and zoonotic potential have not been forwarded. e present work is part of a broader project, in which we assessed, through molecular tools (mitochondrial DNA sequencing), the zoonotic circulation of Strongylida and Ascaris in the human-swine interface in low-resource rural communities in the state of Piauí [15][16][17][18]. In this report, we present the results of the morphological study of Strongylida larvae obtained through cultivation of human and swine feces.…”
Section: Introductionmentioning
confidence: 99%